2018
DOI: 10.1136/openhrt-2018-000909
|View full text |Cite
|
Sign up to set email alerts
|

Absence of chest pain and long-term mortality in patients with acute myocardial infarction

Abstract: ObjectiveChest pain is the predominant symptom in patients with acute myocardial infarction (AMI). A lack of chest pain in patients with AMI is associated with higher in-hospital mortality, but whether this outcome is sustained throughout the first years after onset is unknown. Therefore, we aimed to investigate long-term mortality in patients hospitalised with AMI presenting with or without chest pain.MethodsAll AMI cases registered in the SWEDEHEART registry between 1996 and 2010 were included in the study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 30 publications
3
30
0
1
Order By: Relevance
“…The atypical features of chest pain of non-cardiac origin are considered less urgent and tend to be overlooked and underestimated. Consequently, delayed diagnosis and treatment of these patients, who were eventually diagnosed with acute myocardial infarction (AMI), have known to be associated with unfavorable clinical outcomes [2,[5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The atypical features of chest pain of non-cardiac origin are considered less urgent and tend to be overlooked and underestimated. Consequently, delayed diagnosis and treatment of these patients, who were eventually diagnosed with acute myocardial infarction (AMI), have known to be associated with unfavorable clinical outcomes [2,[5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…There is a lack of evidence on whether atypical chest pain affects long-term clinical outcomes. SWEDEHEART registry included 172,981 AMI patients between 1996 and 2010 [7]. Patients without chest pain were defined as those not having chest pain, including dyspnea and non-specific symptoms.…”
mentioning
confidence: 99%
“…Patients with advanced age may present to EDs with a variety of symptoms potentially suggestive of an ACS [41][42][43]. Of note, patients presenting to EDs without cardiac chest pain but with high HsTnT levels have very high all-cause mortality [44,45]. Other studies have reported that, compared to younger patients, the very elderly frequently do not have typical chest pain as the main presenting symptom for MI [46][47][48].…”
Section: Discussionmentioning
confidence: 99%
“…These routines include biomarker analysis to evaluate the risk of developing CVD or to identify its early onset and are most often conducted in primary care settings. Moreover, a high proportion of deaths attributed to CVD occur in asymptomatic individuals who may have been classified as high-risk following a cardiovascular screening [231,232,233,234]. Several cardiovascular risk estimation systems have been developed to assist in the risk profiling of patients, with Figure 9 depicting an adapted and simplified SCORE risk estimation chart that displays only a limited selection of key risk factors [235,236].…”
Section: Mips For Point-of-care Testingmentioning
confidence: 99%